THE MAIN ASPECTS OF CO-EXISTENCE OF CHRISTIANITY AND PAGANISM IN THE CONTEXT OF ANCIENT RUSSIAN SPIRITUAL CULTURE AND CULT PRACTICE - A. I. Simonov (Концепт: философия, религия, культура, 2019)
This article is devoted to the spiritual culture analysis. More specifically, it examines the mutual influence of Orthodox and pagan principles of the middle ages and subsequently modified into folk religious traditions. Research material is a multi-level system of the ancient Russian religious worldview which is reflected as in liturgical practice and polemic literature of Russian Orthodoxy as in peace and cult activities of the people who have preserved the principles of a pagan worldview.Initially, emphasis was placed on interpretation of the concept of “dual faith” as a simple linear  connection of elements of Orthodox and pagan worldview into something one (E.E. Golubinsky, N.I. Barsov, A.P. Shchapov, M. Azbukin, G.A. Nosova, A.N. Ipatov, A.E. Musinetc.). Then “dual faith” is considered as synthesis of Orthodox and pagan views on the structure of the Universe (E.V. Anitchkov, N.M. Galskovsky etc.). It was found that the spiritual situation of Ancient Russia after the adoption of Christianity reflected the fact of the meeting of two religious trends: affirmation of faith in one God (Orthodoxy) and manifestation of religious syncretism (polytheism of Slavic paganism). The spiritual situation of Ancient Russian culture led to the emergence and cultivation of ideological  struggle that does not deny elements of ideological symbiosis, Orthodox teaching and pagan beliefs. The main message of the controversy is reduction of paganism to demonology and treating it as a deification of the world (deification of nature and man created by God).The struggle (interaction) of the Orthodox and pagan principles in Russian spiritual culture of the middle ages is reduced to stating the following development vectors: the official canonical direction (government acts, the Kormchaya Kniga – religious code, etc.) and polemic direction requiring philosophical reflection and mastery of oratory (messages, teachings church sermon, etc.).“Interaction” of Orthodoxy and paganism involves processes of crowding out and replacing folk and Christian beliefs. Such processes create new spaces for spiritual creativity. This is the birth of Russian spiritual culture.